(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Structural Health Monitoring (SHM) is one of the emerging fields in which smart technology isused to inspect the civil engineeringstructure components to prevent from failure. SHM will detect thefundamental properties such as cracks in the structure and expedite needed repairs, and thus increasethe useful life of those components.The safety measures related to civil engineering structures withrespect to age of the structure, structural damage, climatic conditions like flood, heavy rains,earthquake, etc. is the prime role of the concerned authorized engineers. In the development ofeconomy and society, many structures have been built which should meet the requirement of theserviceability, safety and sustainability during the operation stage throughout its life cycle. But duesome reasons the structure gets weak and cracks starts developing within the components. Graduallythe crack expands which leads the structure to collapse. To avoid the failure of structure the cracksmust be detected at early stage and this could be done by using piezoelectric film. Using IoT ,thepiezoelectric film shows the crack detection on bridge. This was major concern in our findings due towhich we have made an ideology in our research to overcome this problem and to bring up safetymajors in our real-life problems.